2015
DOI: 10.1136/practneurol-2015-001275
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related disease: a rare but treatable cause of refractory intracranial hypertension

Abstract: Hypertrophic pachymeningitis secondary to IgG4-related disease is a rare but sometimes devastating cause of intracranial hypertension. It has the potential for an excellent response to corticosteroids or rituximab. We discuss the clinical presentation, imaging, histology (with its difficult distinction from lymphoma), management and follow-up of a case, including relapse and re-treatment following an initial response to rituximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Hypertrophic pachymeningitis has been recognised as part of the IgG4-related disease spectrum [3], and can present with intracranial hypertension [4], as well as leptomeningitis, hypophysitis, pseudotumor and cranial neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertrophic pachymeningitis has been recognised as part of the IgG4-related disease spectrum [3], and can present with intracranial hypertension [4], as well as leptomeningitis, hypophysitis, pseudotumor and cranial neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…IgG4‐RHP seems to have a similar course to other IgG4‐RD patients. Most IgG4‐RHP respond to corticosteroids, but rapid recurrence of symptoms of HP is reported in different case series necessitating a corticosteroid‐sparing agent such as methotrexate, azathioprine, rituximab, and rarely mycophenolate mofetil 15–17 . As we considered meningeal disease was an urgent condition, all of our cases were treated with pulse corticosteroids, showing clinical improvement.…”
Section: Age At Onset/sex Symptoms Serum Igg4 At Diagnosis (Mg/dl) An...mentioning
confidence: 87%
“…13 A case-control study, suggested that CSF IgG4 quantification could be an alternative diagnostic tool with a cut off value of 2.27 mg/dL. [15][16][17] As we considered meningeal disease was an urgent condition, all of our cases were treated with pulse corticosteroids, showing clinical improvement. Four of them received rituximab, and 1 patient received azathioprine.…”
Section: Mri Dural Thickening Locationmentioning
confidence: 95%